2019
DOI: 10.1556/650.2019.31404
|View full text |Cite
|
Sign up to set email alerts
|

Generalizált epilepszia hátterében azonosított ioncsatorna-génmutáció ritka formája

Abstract: The advances in molecular genetic methods has lead to the discovery of the genetic alterations that underlie the etiology of most diseases previously held to be idiopathic. Targeted genetic examination of a pediatric male patient showing a normal intellect, an extended area of skin hypopigmentation, and suffering from generalized epilepsy displaying a switch in epilepsy syndrome during the course of the disease towards a neurocutaneous syndrome was unsuccessful. Whole-exome sequencing identified a heterozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…No change in membrane expression, L426P, G551D: ↓ expression and glycosylation. Loss Cl extrusion activity [ 51 , 88 ] V473I IGE [ 89 ] S748del, R857L CT EIMFS [ 87 , 88 ] R1048W ASD [ 90 ] R952H, R1049C ASD, SCZ, IGE Impaired transport activity [ 85 , 90 ] R952H Febrile seizures ↓ Cl extrusion. Impaired ability to form dendritic spines.…”
Section: Mutations Associated With Human Diseasesmentioning
confidence: 99%
“…No change in membrane expression, L426P, G551D: ↓ expression and glycosylation. Loss Cl extrusion activity [ 51 , 88 ] V473I IGE [ 89 ] S748del, R857L CT EIMFS [ 87 , 88 ] R1048W ASD [ 90 ] R952H, R1049C ASD, SCZ, IGE Impaired transport activity [ 85 , 90 ] R952H Febrile seizures ↓ Cl extrusion. Impaired ability to form dendritic spines.…”
Section: Mutations Associated With Human Diseasesmentioning
confidence: 99%
“…In addition to the mRNAs with increased expression mentioned above, which are related to cell differentiation and proliferation, the decreased expression of SLC12A5 aroused our interest. SLC12A5 (encoding the KCC2 protein) acts to stabilize nerve cell potential, and its reduced expression correlates with the development of epilepsy ( 34 39 ). Consistent with our findings, Yang and Gao et al found that the expression of SLC12A5 in patients with shorter survival time was significantly lower than that in patients with longer survival ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that reduced KCC2 activity may be involved in the mechanisms underlying increased excitability in the brains of epileptic patients. The identification of various KCC2 mutations (encoded by SLC12A5 ) has further highlighted the association between KCC2 dysfunction and the development of epilepsy [ 41 46 ]. A summary of the KCC2 mutations discovered in human epilepsy can be found in Table 1 [ 47 ], with their localization shown in Fig.…”
Section: The Role Of Kcc2 In Epileptogenesismentioning
confidence: 99%